2017
DOI: 10.7150/jca.18683
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression Is Associated with FOXP3+ Regulatory T-Cell Infiltration of Soft Tissue Sarcoma and Poor Patient Prognosis

Abstract: Background: Programmed death ligand-1(PD-L1) functions as a negative mediator of immune response through different pathways in anti-tumor immunity. Recent studies have reported that PD-L1 plays a pivotal role in the function of regulatory T-cells (Tregs). Although increases in FOXP3+ Tregs infiltration and PD-L1 expression have been revealed in several cancers, their correlation with soft tissue sarcoma remains unknown. Methods: We included 163 cases of soft tissue sarcoma who were diagnosed and underwent exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 39 publications
(34 reference statements)
6
62
0
3
Order By: Relevance
“…A previous report has shown that PD-L1 expression in SM (22,23), and all types of melanoma (24) is associated with CD8 + lymphocytes, consistent with our findings. Furthermore, PD-L1 expression is associated with FOXp3 + lymphocytes in sarcoma (17) and breast cancer (25), consistent with our results. CD8 + lymphocytes as well as PD-L1 expression in tumor cells might be candidate predictive biomarkers for the CIC response.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A previous report has shown that PD-L1 expression in SM (22,23), and all types of melanoma (24) is associated with CD8 + lymphocytes, consistent with our findings. Furthermore, PD-L1 expression is associated with FOXp3 + lymphocytes in sarcoma (17) and breast cancer (25), consistent with our results. CD8 + lymphocytes as well as PD-L1 expression in tumor cells might be candidate predictive biomarkers for the CIC response.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with PD-L1-positive sarcoma are younger than those with PD-L1-negative sarcoma (17), as observed for melanoma in the present study. In contrast, patients with HLA-positive melanomas were older than those with HLA-negative melanomas in the present study.…”
Section: Discussionsupporting
confidence: 79%
“…Although CD4+ lymphocytes did not show any association with the prognosis of patients with SS, in our study, a higher infiltration of FOXP3+ lymphocytes was significantly associated with a better OS. However, Que et al evaluated the infiltration of FOXP3+ lymphocytes in 163 cases of soft tissue sarcoma, including 21 cases of SS, and showed that a higher infiltration of FOXP3+ lymphocytes was associated with a poor prognosis. This result is markedly different from ours.…”
Section: Discussionmentioning
confidence: 99%
“…12 In PDAC, it is referred to as cancer-FOXP3 (C-FOXP3), and its function is to mediate immune evasion by recruiting FOXP3+ T cells (Treg cells) via upregulation of CCL5. Interestingly, accumulating evidence has linked the coexistence of tumor-associated PD-L1 and Treg cell infiltration in multiple tumors, including PDAC, [14][15][16] suggesting that C-FOXP3 may be correlated with PD-L1 expression in PDAC. The regulatory mechanism(s) of PD-L1 expression on pancreatic cancer cells remains poorly investigated.…”
Section: Introductionmentioning
confidence: 99%